POLA INTERAKSI EDUKATIF GURU TAMAN KANAK-KANAK DALAM PROSES BELAJAR MENGAJAR DI TK SE KECAMATAN BANGKINANG KABUPATEN KAMPAR - Novi Anugrah Putri; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The author formulated in this research is how the educative interaction patterns of kindergarten teachers in the learning process in kindergartens in Bangkinang District, Kampar Regency? The purpose of this learning activity is to find out the educative interaction patterns of kindergarten teachers in the teaching and learning process in kindergartens in Bangkinang District, Kampar District. The population referred to in the study are all population objects that are members of the population, namely all teachers in the Bangkinang sub-district which number approximately 250 teachers. The sample in this study were 71 teachers. From the sample of 71 people 20 people were taken for the questionnaire trial sample and the remaining 51 teachers were made into the study sample. The data in this study were obtained through questionnaires to kindergarten teachers in kindergartens in Bangkinang District, Kampar District. Based on the results of the study, it can be concluded that the educative interaction patterns of kindergarten teachers in the teaching and learning process in kindergartens in Bangkinang Subdistrict, Kampar Regency are included in the Excellent category because they have an average of 87.76%.Keywords: patterns of educational interaction